2011
DOI: 10.1371/journal.pone.0026399
|View full text |Cite
|
Sign up to set email alerts
|

CCND1 as a Predictive Biomarker of Neoadjuvant Chemotherapy in Patients with Locally Advanced Head and Neck Squamous Cell Carcinoma

Abstract: BackgroundCyclin D1 (CCND1) has been associated with chemotherapy resistance and poor prognosis. In this study, we tested the hypothesis that CCND1 expression determines response and clinical outcomes in locally advanced head and neck squamous cell carcinoma (HNSCC) patients treated with neoadjuvant chemotherapy followed by surgery and radiotherapy.Methodology and Findings224 patients with HNSCC were treated with either cisplatin-based chemotherapy followed by surgery and radiotherapy (neoadjuvant group, n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 32 publications
2
52
0
Order By: Relevance
“…In HNSCC, high cyclin D1 expression is correlated with chemotherapy failure and poor prognosis (30)(31)(32). In response to G12V HRAS-driven activation of the MAPK pathway, we observed a robust upregulation of cyclin D1 protein levels in UM-SCC1 cells, whereas cyclin D1 levels were only slightly upregulated in UM-SCC25 cells (Fig.…”
Section: The Gene Expression Signature Upon Activation Of the Mapk Pamentioning
confidence: 68%
“…In HNSCC, high cyclin D1 expression is correlated with chemotherapy failure and poor prognosis (30)(31)(32). In response to G12V HRAS-driven activation of the MAPK pathway, we observed a robust upregulation of cyclin D1 protein levels in UM-SCC1 cells, whereas cyclin D1 levels were only slightly upregulated in UM-SCC25 cells (Fig.…”
Section: The Gene Expression Signature Upon Activation Of the Mapk Pamentioning
confidence: 68%
“…Upon phosphorylation, pRb releases the transcription factor E2F, which is then able to activate the transcription of genes required for G1/S phase transition [32]. It has been reported that cyclin D1 is overexpressed in many human cancers including HNSCC, and it is associated with enhanced tumor growth, chemotherapy resistance and poor prognosis [33][34][35]. Thus, suppression of cyclin D1 may be a useful target for the therapy of HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, 75% of Chinese patients already have advanced-stage disease at the time of diagnosis, and more than 76,000 patients die each year. 1 It is well known that lymph node metastases are the most important prognostic factor in head and neck cancer. [2][3][4][5] Recently, it was reported that lymph node yield (LNY) was likely an independent prognostic factor in patients undergoing neck dissection for head and neck squamous cell carcinoma (HNSCC).…”
mentioning
confidence: 99%